Dual Role is Adjusting the Conflict of Employees Women in Pinrang Regency Office - Ali Halidin (Journal of Research and Multidisciplinary, 2019)
Women are the god beings who are equal to the men, who have the will to progress and play an active role in all life and social life. Women with their position as wives lead to the assumption of the community that the place of women only played in the domestic realm, besides being a wife as a housewife whose work is limited by only take care of the household and family. There are not a few women have a strong will to access what is accessible to the men, just as having a job can produce and play an active role in helping the family's economic level. Actually, there is no problem with this, women can be housewives, wives, and workers outside the home. By dividing his time between work and his role at home, but with the helping from the male, as a husband with the concept of dividing roles between wife and husband. The problem that will occur, if the participation of women does not get help even from the husband's support, causing excessive burden is going very difficult and lead to inner conflict in a woman, besides as a wife and housewife as a mandatory work, plus work outside the home which certainly takes a lot time, even this condition can be even worse if the man as his husband refuses his wife's role to work outside the home with consideration of customs and culture or other things, while the household needs cannot be fulfilled optimally, even the possibility of a fatal event can occur in the form of domestic violence by the husband to his wife, which leads to physical conflicts and criminal acts